Stem cells : from bench to bedside - Bongso, Ariff; Lee, Eng Hin, 1947- (World Scientific, 2005)
Stem cell biology has gained tremendous interest in the recent years, driven by the hope of finding cures for several diseases through transplantation medicine. Various types of stem cells have been identified from preimplantation embryos, the fetus, placenta and adult.